2014
DOI: 10.7547/0003-0538-104.5.434
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of the Neglected Achilles Tendon Rupture with Hyalonect

Abstract: For patients with chronic Achilles tendon rupture with a rupture gap of at least 5 cm, surgical repair using a single turndown fascial flap covered with Hyalonect achieved excellent outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…All patients with RCT underwent to double-or single-row arthroscopy for the repair of lesions with different dimensions: small (0-1 cm) in 10% of the studies (Castricini et al, 2011;Rodeo et al, 2012), medium (1-3 cm) in 2/20 studies (Gumina et al, 2012;Weber et al, 2013), full-thickness up to 3 cm (Barber, 2016;Barber, Hrnack, Snyder, & Hapa, 2011;Bergeson et al, 2012;Encalada-Diaz et al, 2011;Jo et al, 2011;Sears, Choo, Yu, Greis, & Lazarus, 2015) in 30%, large (>3 cm), and massive (4-5 cm) in 45% (Badhe, Lawrence, Smith, & Lunn, 2008;Barber, Burns, Deutsch, Labbé, & Litchfield, 2012;Bond, Dopirak, Higgins, Burns, & Snyder, 2008;Cho, Lee, Lee, & Shin, 2014;Ciampi et al, 2014;Jo et al, 2013;Rotini et al, 2011;Russo, Lombardi, Visconti, & Della, 2011;Wong, Burns, & Snyder, 2010). On the other hand, all patients with Achilles tendon ruptures (Basiglini, Iorio, Vadalà, Conteduca, & Ferretti, 2010;Bibbo, 2010;Branch, 2011;DeCarbo, Feldner, & Hyer, 2010;Elias, Raikin, Besser, & Nazarian, 2009;Esenyel et al, 2014;Ibrahim, 2009;Kearney & Costa, 2010;Lee, 2008;Nilsson-Helander et al, 2008;Ollivere, Bosman, Bearcroft, & Robinson, 2014;Stover, Zelen, & Nielson, 2009;Wegrzyn et al, 2010) were operated with suture techniques for acute (7/13 studies) (Basiglini et al, 2010;Bibbo, 20...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All patients with RCT underwent to double-or single-row arthroscopy for the repair of lesions with different dimensions: small (0-1 cm) in 10% of the studies (Castricini et al, 2011;Rodeo et al, 2012), medium (1-3 cm) in 2/20 studies (Gumina et al, 2012;Weber et al, 2013), full-thickness up to 3 cm (Barber, 2016;Barber, Hrnack, Snyder, & Hapa, 2011;Bergeson et al, 2012;Encalada-Diaz et al, 2011;Jo et al, 2011;Sears, Choo, Yu, Greis, & Lazarus, 2015) in 30%, large (>3 cm), and massive (4-5 cm) in 45% (Badhe, Lawrence, Smith, & Lunn, 2008;Barber, Burns, Deutsch, Labbé, & Litchfield, 2012;Bond, Dopirak, Higgins, Burns, & Snyder, 2008;Cho, Lee, Lee, & Shin, 2014;Ciampi et al, 2014;Jo et al, 2013;Rotini et al, 2011;Russo, Lombardi, Visconti, & Della, 2011;Wong, Burns, & Snyder, 2010). On the other hand, all patients with Achilles tendon ruptures (Basiglini, Iorio, Vadalà, Conteduca, & Ferretti, 2010;Bibbo, 2010;Branch, 2011;DeCarbo, Feldner, & Hyer, 2010;Elias, Raikin, Besser, & Nazarian, 2009;Esenyel et al, 2014;Ibrahim, 2009;Kearney & Costa, 2010;Lee, 2008;Nilsson-Helander et al, 2008;Ollivere, Bosman, Bearcroft, & Robinson, 2014;Stover, Zelen, & Nielson, 2009;Wegrzyn et al, 2010) were operated with suture techniques for acute (7/13 studies) (Basiglini et al, 2010;Bibbo, 20...…”
Section: Resultsmentioning
confidence: 99%
“…Thirty percent of the studies regarding RCT reached a maximum follow-up of 12 months (Barber, 2016;Bergeson et al, 2012;Encalada-Diaz et al, 2011;Rodeo et al, 2012;Rotini et al, 2011;Weber et al, 2013), while 1 (Basiglini et al, 2010) study evaluated outcomes at 12 months in Achilles tendon ruptures. Studies that exceeded 36 months of follow-up were five in RCT studies (44, 60, 68, or 112 months and 16 years;Badhe et al, 2008;Barber et al, 2011;Russo et al, 2011;Sears et al, 2015;Wong et al, 2010) and six (41, 60, 68, 81, and 117 months;Bibbo, 2010;Elias et al, 2009;Esenyel et al, 2014;Ibrahim, 2009;Nilsson-Helander et al, 2008;Wegrzyn et al, 2010) in Achilles tendon ones. Only one study showed a follow-up earlier than 12 months in RCT (Snyder et al, 2009) and five studies in Achilles tendon (3, 6, and 9 and 11 months;Branch, 2011;DeCarbo et al, 2010;Kearney & Costa, 2010;Ollivere et al, 2014;Stover et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations